L´Elettrice Palatina: Mecenetismo, coleccionismo, formación y la misión del museo - Cavagnaro Farfán, Franco (2019)
This article is a critical and creative review of the proceedings of the celebrations that, over his life and legacy, took place between 2002 and 2004 and which were published in Florence by the Polistampa publishing house with the title: Anna Maria Luisa de ‘ Medici elettrice palatina: atti delle celebrazioni, 2002-2004, Palazzo Vecchio, Firenze, under the coordination of Anita Valentini. The particularity of this work lies in the epistemological crossing that takes place to see in it the origin of public museums, in the legacy that the elector Anna Maria Luisa de’ Medici made so that the medicea collection (of arts, books, scientific instruments) did not disperse, nor was hoarded by a family or alienated